The Providence of Review and Writing through Revision. - Canham, Hugo ka (African Studies)
In the uneven publishing landscape between Africa and the global north publishing industry, almost all editorial rejections or requests for revision are initially narcissistically injurious. They compel one to pause, to revisit their views, and perhaps they make writers second guess themselves. In this paper, I focus on review feedback as a productive pause. I think with the affects and potentialities that follow the initial injury. I posit that if we look past the wounding, most revisions can be transformed into practices of care. I contemplate what it means for one's work to be attended to by others and the generative possibilities that different lenses might enable. This thrust to focus on the positive is not to dismiss the epistemic violences that being revised and corrected might enact. Instead, I suggest that as writers committed to our craft and ideas, we might mine the review process for glimmers of care even if this entails rummaging through the dregs of callous feedback. Focusing on two writing projects, I think about iterative review as involving a wide network of readers that include formal reviewers and informal readers that are part of a reading community of practice. I suggest that conceived of broadly, reviewers might mediate the writing process in ways that nurse underdeveloped ideas, push us beyond parochial reading practices, and widen the resonance of our work beyond our initial imaginaries. To read the review and publication process through body politics and geopolitics as potentially inhibiting and enabling, propels us beyond binaries and broadens the scope of review to consider the roles of our informal readers. Conceived of this way, review is an important part of the practice of writing. It enhances our craft, ideas and political commitments.